2015
DOI: 10.1021/acs.jpcc.5b01223
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Nearest-Neighbor Interactions To Alter Charge Transport Mechanisms in Molecular Assemblies of Porphyrins on Surfaces

Abstract: This document includes details on the synthesis of the molecule used in this study and its associate characterization along with additional details on the monolayer characterization by FTIR and XPS and additional details on the DFT calculations employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 86 publications
(138 reference statements)
1
31
0
Order By: Relevance
“…We have shown 50,177 that click chemistry can be used to append thioalkyl tethers which can be attached to the Au surface for rapid assessment of chain length and dye association (Fig. 27).…”
Section: Substituted Fluorinated Porphyrinoids For Application In Matmentioning
confidence: 99%
“…We have shown 50,177 that click chemistry can be used to append thioalkyl tethers which can be attached to the Au surface for rapid assessment of chain length and dye association (Fig. 27).…”
Section: Substituted Fluorinated Porphyrinoids For Application In Matmentioning
confidence: 99%
“…[33] It is also noticeable from Figure 7a nd Figures S10a-c that the peak current is almost proportional to n,d emonstratingt hat intra-or intermolecular electron hopping fromt he second to the first layer is faster than electron transfer to the electrode, and therefore extremely efficient. [33] It is also noticeable from Figure 7a nd Figures S10a-c that the peak current is almost proportional to n,d emonstratingt hat intra-or intermolecular electron hopping fromt he second to the first layer is faster than electron transfer to the electrode, and therefore extremely efficient.…”
Section: Ultrafast Electron Transfermentioning
confidence: 79%
“…21 Studies were reported by Schuckman et al of the charge transport properties of a tethered Zn(II) porphyrin thiol complex, tripyridyl porphyrin, in which molecular clusters were inserted within an alkanethiol matrix on Au(111). 22,23 …”
Section: Introductionmentioning
confidence: 99%